2021
DOI: 10.1177/1084822321992380
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Existing Inequality: The Impact of COVID-19 on Medicare Home Health Beneficiaries

Abstract: There is significant data on the adverse impact of COVID-19 on persons who were poor, minorities, had compromised physical or mental health, or other vulnerabilities prior to the COVID-19 pandemic. A significant portion of the overall Medicare population has such vulnerabilities. The Medicare home health beneficiary population is even more vulnerable than the overall Medicare population based on gender, race, income level, living alone status, and number of chronic conditions. A literature review indicates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…These results also indicated that the agencies’ inability to manage the situation even intensified the crisis. Since crisis management is vital in controlling critical situations [ 28 ], there must be some schemes implemented prior to the crisis in order to control it at the right time [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results also indicated that the agencies’ inability to manage the situation even intensified the crisis. Since crisis management is vital in controlling critical situations [ 28 ], there must be some schemes implemented prior to the crisis in order to control it at the right time [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature explored the reasons for service changes in HHAs or certified HHA agencies (Cabin, 2021; Shang et al, 2020; Sterling et al, 2020), not nurses' assessment of these changes or the implication of those changes. Cabin (2021) and Shang et al (2020) described specific reasons for changes in home health agency services including staffing shortages secondary to staff illnesses or having to care for an ill family member or having to care for children secondary to school closure; lack of appropriate personal protective equipment; families of patients not wanting the services and taking over the care themselves to avoid the risk of transmission; and decreased agency patient census and subsequent staffing layoffs. We include similar changes in home-based diagnostic services like a home laboratory or home imaging services that were not addressed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous issue of this journal, the author addressed the literature gap by presenting a study on home care nurses' perceptions of the impact of COVID-19 on Medicare home health beneficiaries. 1 However, the previous study did not present perceptions of social workers who are the primary professionals responsible for home health beneficiaries psychosocial and social needs. This study reflects social worker perceptions based on interviews conducted July 1, 2020 through September 30, 2020.…”
Section: Introductionmentioning
confidence: 90%
“…In a previous issue of this journal, the author addressed the literature gap by presenting a study on home care nurses' perceptions of the impact of COVID-19 on Medicare home health beneficiaries. 1 The current study is a companion qualitative study to the nurses' study.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation